Perlindungan Hukum terhadap Konsumen dalam Transaksi Live Shopping di Platform Digital - Kunarso Kunarso; Dicky Hartono; Rena Fandani; Michael Fredson Soselisa (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2026)
The development of digital technology has transformed trading patterns through the emergence of live shopping, a phenomenon that enables real-time interaction between sellers and consumers. Although it offers marketing efficiency, this model poses significant legal risks, including misleading information, promotional manipulation, and product non-conformity. This study aims to analyze legal certainty in consumer protection within live shopping transactions, examine the forms of business actors’ liability for consumer losses, and identify obstacles to regulatory implementation along with efforts to strengthen supervision.The research method employed is normative legal research using both a statute approach and a conceptual approach. The results indicate that legal certainty in consumer protection within this ecosystem is grounded in the integration of Law No. 8 of 1999 (Consumer Protection Law) as the lex generalis and Government Regulation No. 80 of 2019 (Electronic Commerce/PMSE) as the lex specialis, which recognizes the validity of real-time electronic contracts. The legal liability of business actors is strict liability in nature, in accordance with Article 19 of the Consumer Protection Law, and may also be construed as a tort (Article 1365 of the Civil Code) in cases involving distortion of visual information.However, the effectiveness of these regulations is hindered by the ephemeral nature of transactions and low levels of digital literacy. This study recommends the implementation of technology-based supervisory systems (suptech), strengthening the oversight function of platforms (PPMSE), and policy synchronization between the Ministry of Trade and the Ministry of Communication and Informatics in standardizing business actor verification to ensure the security of the digital commerce ecosystem.